Occurrence of the alien nudibranch Melibe viridis (Kelaart, 1858) (Opisthobranchia, Tethydidae), in the Maltese Islands - BORG, J.A.; EVANS, J.; SCHEMBRI, P.J. (Mediterranean Marine Science, 2009)
The alien dendronotacean nudibranch Melibe viridis (Kelaart, 1858), a tropical Indo-Pacific species that seems to have been introduced by shipping into the Mediterranean via the Suez Canal, and which has established populations in Greece, Turkey, Cyprus, Montenegro, Croatia, NW Sicily, southern peninsular Italy and Djerba Island in the Gulf of Gabes, is recorded for the first time from Malta. A thriving population was observed on a soft sediment bottom at a depth of 18-20 m off the western coast of the island of Comino (Maltese Islands). It is suggested that this species was introduced into Malta due to a natural range expansion of surrounding populations.